SEVENTEEN YEARS OF CIGARETTE PROBLEM IN INDONESIA: HOW IS THE DISTRIBUTION? - Prasetya Astuti, Aldiella Ayu; Puspita Devi, Yuli; Mega Kurnia, Galuh; Satya Dewi, Rika (Jurnal Biometrika dan Kependudukan, 2025)
Indonesia is ranked first as the country with the highest smoking prevalence in ASEAN. The aims of this study is to find prioritized areas with smoking problems in Indonesia in the last seventeen years (2007-2023).  Research uses secondary data from Basic Health Research 2007, 2010, 2013, 2018, and the 2023 Indonesian Health Survey. The smoking problem in Indonesia is shown through the variables of smoker prevalence and the average cigarettes smoked per day. Data was mapped using the QGIS application.  The result show that there is a downward trend in smoking prevalence and the average number of cigarettes smoked per day in all provinces. The highest peak for smoking problems, where all provinces were in the high category for both variables in 2010. The provinces of West Java and West Nusa Tenggara need to receive attention because the prevalence of smoking is always in the high category from 2007 to 2023.  The conclusion is  that the distribution of smoking problems in Indonesia in the last 17 years shows that the provinces of West Java and West Nusa Tenggara are provinces that are consistently in the high category. Further research needs to be done on the factors that influence the high prevalence of smokers in West Java and West Nusa Tenggara, as well as the effectiveness of government policy implementation in these two provinces.